2019
DOI: 10.1111/imr.12821
|View full text |Cite
|
Sign up to set email alerts
|

Impaired B‐cell tolerance checkpoints promote the development of autoimmune diseases and pathogenic autoantibodies

Abstract: A role for B cells in autoimmune diseases is now clearly established both in mouse models and humans by successful treatment of multiple sclerosis and rheumatoid arthritis with anti-CD20 monoclonal antibodies that eliminate B cells. However, the underlying mechanisms by which B cells promote the development of autoimmune diseases remain poorly understood. Here, we review evidence that patients with autoimmune disease suffer from defects in early B-cell tolerance checkpoints and therefore fail to counterselect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 143 publications
(266 reference statements)
1
108
0
1
Order By: Relevance
“…In the area of autoimmunity, increased circulating NF-B cells are found in SLE, type 1 diabetes, and juvenile dermatomyositis (28,29) possibly as an important source of pathogenic autoantibodies. It is suggested that autoreactive NF-B cells contains clones that may develop into CD27 − CD21 −/lo B cells after the acquisition of somatic hypermutations that improve affinity for self-antigens (27). In adults, we observed an inverse relationship between increased CD21 lo B cells and decreased T1 B regs, suggesting a possible inhibitory impact of B reg cells on CD21 lo B cells at the early B cell checkpoint.…”
Section: Age Related B Cell Differencesmentioning
confidence: 54%
See 2 more Smart Citations
“…In the area of autoimmunity, increased circulating NF-B cells are found in SLE, type 1 diabetes, and juvenile dermatomyositis (28,29) possibly as an important source of pathogenic autoantibodies. It is suggested that autoreactive NF-B cells contains clones that may develop into CD27 − CD21 −/lo B cells after the acquisition of somatic hypermutations that improve affinity for self-antigens (27). In adults, we observed an inverse relationship between increased CD21 lo B cells and decreased T1 B regs, suggesting a possible inhibitory impact of B reg cells on CD21 lo B cells at the early B cell checkpoint.…”
Section: Age Related B Cell Differencesmentioning
confidence: 54%
“…The tissue distribution of cGvHD in the two cohorts was different, in that skin and lung cGvHD was more common in the adult population compared to the pediatric cohort. Atypical cGvHD presentations not associated with the diagnostic criteria 1411 (25) 12 (27) We have previously analyzed these two cohorts separately and published the results (4,8,18). While the pediatric analysis is only focused on immune profiles at day 100 post HSTC (8) and measured before the onset of cGvHD, and published adult results (4) were measured at the onset of cGvHD, we felt we could identify age-related patterns to guide additional comparisons of the two cohorts.…”
Section: Description Of the Pediatric And Adult Population Utilized Imentioning
confidence: 99%
See 1 more Smart Citation
“…In immune system, B cells are classically recognized as positive modulators to regulate inflammation and immune responses by releasing antibodies and activating T cells through antigen presentation (1)(2)(3). Generally, B cells produce antibodies which are a critical part of the host immunity against infection, that can neutralize pathogens, opsonize pathogens for subsequent phagocytosis and mediate antibody-dependent cellular cytotoxicity (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…This highly activated process of differentiation to ASCs is believed to be induced by the disruption of tolerance checkpoints, which promotes survival of autoreactive ASCs with increasing quantities of autoantibodies [7][8][9]. Through the detection of B cells that recognize nuclear antigens (ANA + B cells) using flow cytometry, the checkpoints between transitional/naïve and naïve/memory cells have been identified in SLE and healthy individuals but naïve ANA + compartments are defective in SLE [10].…”
Section: Introductionmentioning
confidence: 99%